THE ROLE OF KIAI HAJI DAILAMI AHMAD IN THE ESTABLISHMENT OF A FORMAL SCHOOL IN BANYUWANGI 1965-2015 - Hervina Nurullita; Agus Mursidi; Aris Susiyanto (International Jurnal of Education Schoolars, 2021)
Kiai is always synonymous with the owner of the pesantren or someone who is in education at the pesantren. Pesantren education was originally used to learn to deepen religious teachings. But along with the times, in pesantren education, general knowledge is also taught which is needed at that time. is Kiai Dailami Ahmad, a figure in Banyuwangi who pays more attention to religious education and formal education with formal education from elementary, middle and high levels. The question of this research is how the participation of Kiai Dailami in formal schools in Banyuwangi in the period 1965-2015. The purpose of this study is to determine the gait of a kiai who is not only involved in Islamic boarding schools but also in the world of formal education. This study uses the historical method which consists of four stages, namely heuristics, criticism, interpretation, and historiography. The result of this research is that Kiai Dailami's persistence in establishing Madrasah Ibtidaiyah, Madrasah Tsanawiyah and Madrasah Aliyah needs to be appreciated. With many failures, however, Kiai Dailami was able to realize the establishment of a school that was beneficial for him.